P09.15 Patient-derived head and neck tumor slice cultures – a versatile tool to study oncolytic virus action. (21st September 2022) - Mayr, M; Runge, A; Schwaiger, T; Sprung, S; Chetta, P; Gottfried, T; Dudas, J; Greier, M; Glatz, M; Haybaeck, J; Elbers, K; Riechelmann, H; et al.
Abstract : Background: Translating preclinical data from cell-based in vitro systems and syngeneic mouse tumor models to the clinically heterogeneous ecosystem of human tumors is a challenging task. Especially head and neck squamous cell carcinomas (HNSCC) show a highly diverse and complex architecture which makes the prediction of a treatment outcome quite difficult. To bridge this gap, we have established and employed a patient-derived HNSCC slice culturing system to assess immunomodulatory effects as well as permissivity and oncolytic virus (OV) action. Materials and Methods: HNSCC tumor biopsies from 12 patients were sectioned using a vibratome and cultured under different conditions for 48hrs. Tumor content and viability of the cultured slices was assessed by two independent pathologists. Characterization of the morphology and tumor microenvironment was done by immunofluorescence stainings. Presence and activation of T-cells upon stimulation either with a bispecific EpCAM-CD3 antibody or a combination of α-CD3/α -CD28 antibodies was analyzed with flow cytometry and measuring IFNy secretion. Permissivity of an oncolytic virus, VSV-GP, in these HNSCC slices was tested using a GFP-tagged OV by following the infection for 48hrs. Co-immunofluorescent studies were performed to analyze which cell populations could be infected by the OV. Results: The heterogenous morphology of a human tumor could be retained in these slice cultures including the preservation of different cell types like tumor cells, immune cells and cancer-associated fibroblast. Upon stimulation with different antibodies the remaining cytotoxic T-cells showed functionality and could be activated. In addition, more than half of the HNSCC slice cultures were permissive to VSV-GP, so they were not only susceptible to the OV but could also produce new progeny. VSV-GP could not only infect epithelial tumor cells but also cells of the tumor microenvironment like stromal cells. Conclusions: This HNSCC slice culturing system is a ex vivo platform that might complement pre-clinical studies to eventually investigate cancer immune-related drugs and ease the translation to the clinics. Disclosure Information: M. Mayr: A. Employment (full or part-time); Significant; ViraTherapeutics. A. Runge: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; ViraTherapeutics. T. Schwaiger: A. Employment (full or part-time); Significant; ViraTherapeutics. S. Sprung: None. P. Chetta: A. Employment (full or part-time); Significant; Boehringer-Ingelheim. T. Gottfried: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; ViraTherapeutics. J. Dudas: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; ViraTherapeutics. M. Greier: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; ViraTherapeutics. M. Glatz: A. Employment (full or part-time); Significant; ViraTherapeutics. J. Haybaeck: None. K. Elbers: A. Employment (full or part-time); Significant; ViraTherapeutics. H. Riechelmann: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; ViraTherapeutics. P. Erlmann: A. Employment (full or part-time); Significant; ViraTherapeutics. M. Petersson: A. Employment (full or part-time); Significant; ViraTherapeutics.